Predictive Accuracy of a Clinical Model for Carriage of Pathogenic/Likely Pathogenic Variants in Patients with Dementia and a Positive Family History at PUMCH - Jialu Bao; Yuyue Qiu; Tianyi Wang; Li Shang; Shanshan Chu; Wei Jin; Wenjun Wang; Yuhan Jiang; Bo Li; Yixuan Huang; Bo Hou; Longze Sha; et al. (Biomedicines)
Background and Objectives: Identifying carriers of Pathogenic/Likely Pathogenic Variants in patients with dementia is crucial for risk stratification, particularly in individuals with a family history. This study developed and validated a clinical prediction model using whole-exome sequencing-confirmed cohorts. Methods: A total of 601 Chinese patients with dementia and a family history were enrolled at Peking Union Medical College Hospital, with 476 in a retrospective derivation cohort and 125 in a temporal validation cohort. Predictive factors included age at onset, APOE ε4 status, and family history characteristics. Model performance was assessed using discrimination and calibration metrics. Results: In the derivation cohort (median age at onset 66 years), 10.3% carried Pathogenic/Likely Pathogenic Variants. Among patients with dementia, those with age at onset < 55 years (OR 2.56, p = 0.0098), more than two affected relatives (OR 3.32, p = 0.0039), parental disease history (OR 4.72, p = 0.015), and early-onset cases in the family (OR 2.61, p = 0.0096) were positively associated with Pathogenic/Likely Pathogenic Variant carriage, whereas APOE ε4 carriage was inversely associated (OR 0.36, p = 0.0041). The model achieved an area under the curve of 0.776 (95% CI, 0.701–0.853) in the derivation cohort and 0.781 (95% CI, 0.647–0.914) in the validation cohort (median age at onset 58 years), with adequate calibration. Conclusions: This model demonstrated strong predictive performance for Pathogenic/Likely Pathogenic Variant carriage, supporting its clinical utility in guiding genetic testing. Further research is needed to refine the model.